Experimental and Analytical Study on the Structural Performance of RC Frame Strengthened with High Energy Dissipating Concrete Jacket - Habib, Ahed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Nowadays, many researches are focused on investigating rubberized concrete as a structural material due to its enhanced properties such as ductility, energy dissipation and damping ratio and its role in the sustainability development by recycling nonbiodegradable waste and reducing the amount of natural aggregates in concrete mixture. However, its performance in retrofitting is still unclear and need to be addressed in order to be implemented in the construction activities. Therefore, the main objective of this research is to investigate the seismic performance of reinforced concrete buildings strengthened using rubberized concrete jackets under severe earthquake excitations. As part of the study, laboratory tests were conducted to evaluate the properties of high-performance self-compacting rubberized concrete mixes with various rubber contents. Furthermore, a reinforced concrete finite element models retrofitted with these concrete mixes were analyzed using nonlinear response history analysis to examine its performance in comparison to control models. The results of this experimental work showed that there is indeed a significant drop in the mechanical properties of concrete will there is a considerable improvement in the damping ratio this improvement affected in the energy dissipation of the structural building where it contributed to increasing the damping energy and reducing the hysteretic one.

ÖZ: Günümüzde, birçok araştırma kauçuklu betonun süneklik, enerji dağıtımı ve sönümleme oranı gibi gelişmiş özelliklerinden ve biyolojik olarak çözünmeyen atığın geri dönüştürülmesi ve betondaki karışımın doğal agrega miktarının azaltılması yoluyla sürdürülebilirlik gelişimindeki rolü nedeniyle yapısal bir malzeme olarak araştırılmasına odaklanmıştır. Ancak, güçlendirme konusundaki performansı hala belirsizdir ve bu yüzden inşaat faaliyetlerinde uygulanabilmesi için ele alınması gerekmektedir. Bu nedenle, bu araştırmanın temel amacı, şiddetli deprem salınımları altında kauçuk beton karışım ceketleri kullanılarak güçlendirilmiş betonarme binaların sismik performansını araştırmaktır. Çalışmanın bir parçası olarak, kendiliğinden yerleşen kauçuklaştırılmış beton ve çeşitli kauçuk içerikli karışımlarının özelliklerini değerlendirmek için laboratuar testleri yapılacaktır. Ayrıca, bu beton karışımlarına uyarlanmış betonarme çerçeveli sonlu eleman modelleri, kontrol modellerine kıyasla performansını incelemek için doğrusal olmayan zaman geçmiş analizi kullanılarak analiz edilecektir. Bu deneysel çalışmanın sonuçları, betonun mekanik özelliklerinde gerçekten önemli bir düşüş olduğunu, ancak diğer yandan, sönümleme oranında önemli bir gelişme olduğunu göstermiştir. Bunu yaparak, sönümleme enerjisinin arttırılması ve histeretik tepkinin azaltılması yoluyla yapıların enerji harcanma kapasiteleri artar.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Co-Supervisor: Prof. Dr. Özgür Eren, Supervisor: Asst. Prof. Dr. Umut Yıldırım.
Keywords: Seismic Design; Buildings - Earthquake effects--Earthquake resistant design; Buildings, Rubberizeed Concrete; Civil engineering--Materials; Rubberized concrete; reinforced concrete jacketing; damping; structure material; energy dissipation; concrete properties; nonlinear response history analysis